2021
DOI: 10.1128/mbio.02220-21
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Microbial Metabolite Leupeptin in the Treatment of COVID-19 by Traditional Chinese Medicine Herbs

Abstract: A TCM formula has played an important role in the treatment of COVID-19 in China. However, the mechanism of TCM action is still unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…The results showed that PF-07321332 has a potent inhibition, with the IC 50 value against the M pro of SARS-CoV-2 being 0.023 μM ( Fig. 1 ), which is much lower than that of recently reported covalent inhibitors such as boceprevir, leupeptin, and carmofur ( 17 , 23 , 24 ).…”
Section: Resultsmentioning
confidence: 69%
“…The results showed that PF-07321332 has a potent inhibition, with the IC 50 value against the M pro of SARS-CoV-2 being 0.023 μM ( Fig. 1 ), which is much lower than that of recently reported covalent inhibitors such as boceprevir, leupeptin, and carmofur ( 17 , 23 , 24 ).…”
Section: Resultsmentioning
confidence: 69%
“…Pharmaceutics 2022, 14, 603 2 of 13 Natural products have great potential to treat SARS-CoV-2 [5], among which plantderived medicines, including the lung cleansing and detoxifying decoction with 21 ingredients, have been used against COVID-19 in China [6,7]. Matrine (MAR), a representative quinolizidine alkaloid from Sophora flavescens Ait, has been used to treat chronic hepatitis and enteritis for years in China (Scheme 1, Table S1) [8].…”
Section: Introductionmentioning
confidence: 99%
“…5MQY is a high-resolution human CTSL protein structure cocrystallized with a covalent inhibitor, compound 35. Since the Z-FA-FMK, Calpeptin, Mg-101(ALLN), Mg-132 and Leupeptin Hemisulfate are all covalent inhibitors [44] , [45] , [46] , [47] , we performed covalent docking available in Schrödinger suite: CovDock in Schrödinger 2021-2 version. To verify the stability of the method, we separated the protein and ligand in 5MQY and performed re-docking calculations with them.…”
Section: Resultsmentioning
confidence: 99%